Oil and Non-oil Export and its Impact on Economic Performance in Saudi Arabia - Abdulrahman, Badreldin Mohamed Ahmed (International Journal of Energy Economics and Policy, 2020)
Oil and non-oil export played essential role in economic activity in Saudi Arabia with amount average of 841816.0 and 162654.6 Saudi riyal respectively in the period 2005- 2019. This study investigates from an empirical point of view the impact of oil and non-oil export on economic performance in Saudi Arabia during the period 2005 to 2019. Data were collected from General Authority for Statistics (GAS) in Kingdom of Saudi Arabia. Ordinary least square method has been applied to estimate linear and non-linear form of the study models. The obtained results showed that oil export and non-oil export have positive impact on economic performance in Saudi Arabia during period of the study. Keywords: oil export, non-oil export, economic performance. JEL Classifications: B22, E23, F13, F43, O11. DOI: https://doi.org/10.32479/ijeep.10311